Environmental and Socioeconomic Determinants of Virtual Water Trade of Grain Products: An Empirical Analysis of South Korea Using Decomposition and Decoupling Model - Golden Odey; Bashir Adelodun; Seulgi Lee; Khalid Adeola Adeyemi; Gunho Cho; Kyung Sook Choi (Agronomy, 2022)
The world’s sustainable growth is being severely hampered by the inefficient use of water resources. Despite the widely acknowledged importance of trade in global and regional water and food security, societal reliance on local production, as well as international trade, remains inadequately assessed. Therefore, using South Korea as a case study, this study fills in this research gap by applying the virtual water concept, the logarithmic mean divisia index (LMDI) method, and the Tapio decoupling model. The virtual water concept was used to estimate South Korea’s net virtual water trade for major grain crops from 1992 to 2017. Then, the LMDI method was utilized to assess the driving factors causing changes in net virtual water trade. Lastly, the Tapio decoupling model was used to investigate the decoupling relationships between economic growth and the driving factors of net virtual water trade. The results showed that South Korea remains a net importer of virtual water flows with respect to grain crops, with an average import of 16,559.24 million m3 over the study period. In addition, the change in net virtual water trade could be attributed to the water intensity effect, product structure effect, economic effect, and population effect. However, water intensity and economic effects were the major decisive factors for decreases and increases in net virtual water trade, respectively, while the population and product structure effects had minor positive influences on the net virtual water trade. Furthermore, water intensity and economic growth showed a strong decoupling in most periods, while the decoupling state between product structure and economic growth was observed as expansive negative decoupling. Likewise, population size and economic growth showed a weak decoupling in most periods. The results reveal South Korea’s status as it concerns the virtual water trade of grain crops, thus providing valuable insights into the sustainability of trade activities for the management of local water resources.